Sanksi Pidana Perbuatan Sengaja Menyalahgunakan Senjata Api Oleh Anggota Kepolisian Negara Republik Indonesia - Gerald Gary Moniharapon; Juanrico Alfaromona Sumarezs Titahelu; Elias Z Leasa (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Possession of firearms is necessary for professional Polri members because the goal is to support their duties.Purposes of the Research: Explaining What is the legal reason for the judge's ruling on the District Court and the High Court's ruling against the perpetrator who intentionally misused a firearm. Methods of the Research: The type of research used is normative juridical. The problem approach used is the statutory approach, namely the approach to legal products and the case approach.Results of the Research: Based on the results of the study, it can be concluded that related to the theory of intentionality (Dolus), the defendant Elianth Ronalto Latuheru's actions have fulfilled the intentional element as a possibility (opzet bij mogelijkheids-bewustzijn). or judge's opinion. Thus stating Ronal Elianth Latuheru, committed a crime of murder with a prison sentence of 8 (eight) years and a Recommendation for Disrespectful Dismissal (PTDH) as a member of the Police.